OPERATION OF THE RADIOLOCATION ANGULAR SYSTEM IN THE CONDITIONS OF THE SIGNAL CREATED BY COHERENT SOURCES OF RADIATION FROM TWO SPOTS - A. A. Dyatko; S. M. Kostromitski; P. N. Shumski; I. N. Davydenkо (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The purpose of the work, the results of which are presented within the framework of the article, was to analyze the operation of the radar goniometer system under the conditions of a signal generated by coherent radiation sources from two points in space (cross-eye interference). To achieve the goal in the present work, a study was made of the dependence of the settings of the goniometric system on the ratio of the parameters of the cross-eye jammer and the angular coordinate meter itself. As a goniometric system, an angular coordinate meter was used, operating by the method of amplitude instantaneous signal comparison. The studies were carried out by the method of theoretical analysis of the influence of the radiation pattern parameters of the antenna system of the meter on the result of measuring the angular position of a virtual radiation source. As a result, an equation is obtained that relates the angular position of the virtual radiation source with the radiation pattern parameters of the antenna system of the meter, the shape of which was approximated by a gaussian curve. To illustrate the functioning of the goniometric system at specific values of the parameters supplied to its input signals, the method of mathematical modeling was used. Modeling was performed for the given parameters, which determine both the position of the radiation sources in space and the algorithm of operation of the angular coordinate meter. Based on the results obtained, it is shown that the angular coordinate meter has three stationary states corresponding to the position of the virtual radiation source in space. It is shown that only two of these states are stable. The latter means that, depending on the initial conditions, the angular coordinate meter can fix one of the two possible positions of the virtual radiation source in space. The scientific novelty of this work is to establish a relationship between the position of the virtual radiation source in space and the parameters of the angular coordinate meter.